2010
DOI: 10.1093/glycob/cwq192
|View full text |Cite
|
Sign up to set email alerts
|

Desulfovibrio desulfuricans PglB homolog possesses oligosaccharyltransferase activity with relaxed glycan specificity and distinct protein acceptor sequence requirements†

Abstract: Oligosaccharyltransferases (OTases) are responsible for the transfer of carbohydrates from lipid carriers to acceptor proteins and are present in all domains of life. In bacteria, the most studied member of this family is PglB from Campylobacter jejuni (PglB(Cj)). This enzyme is functional in Escherichia coli and, contrary to its eukaryotic counterparts, has the ability to transfer a variety of oligo- and polysaccharides to protein carriers in vivo. Phylogenetic analysis revealed that in the delta proteobacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 32 publications
0
52
0
Order By: Relevance
“…However, recent reports on C. jejuni, Haemophilus influenzae, and Desulfovibrio desulfuricans N-glycosylations indicate that there is no conserved core structure in bacteria (Gross et al, 2008;Ielmini & Feldman, 2011;Young et al, 2002). Thus, in prokaryotes many different glycoprotein structures have been observed that display much more variation than those observed in eukaryotes.…”
Section: Protein Glycosylationmentioning
confidence: 99%
“…However, recent reports on C. jejuni, Haemophilus influenzae, and Desulfovibrio desulfuricans N-glycosylations indicate that there is no conserved core structure in bacteria (Gross et al, 2008;Ielmini & Feldman, 2011;Young et al, 2002). Thus, in prokaryotes many different glycoprotein structures have been observed that display much more variation than those observed in eukaryotes.…”
Section: Protein Glycosylationmentioning
confidence: 99%
“…Recently released bacterial genome sequence data indicate that many members of the Deltaproteobacteria-Epsilonproteobacteria subdivision of the Proteobacteria contain pglB orthologues (13,15,25,37,44). Prominent genera within the Epsilonproteobacteria subdivision include Arcobacter, Campylobacter, and Helicobacter.…”
mentioning
confidence: 99%
“…A PglB orthologue from the d-proteobacterium Desulfovibrio desulfuricans was also recently functionally characterized. DdPglB was shown to transfer the C. jejuni heptasaccharide to the acceptor protein AcrA in the recombinant E. coli system (Ielmini & Feldman, 2011). However, a distinct difference in acceptor site specificity was detected.…”
Section: Identification Of Novel Bacterial N-glycosylation Machineriementioning
confidence: 96%
“…Only one asparagine residue was modified by DdPglB and mass spectrometry analysis of the acceptor site revealed the presence of a short, eukaryotic-like NXS/T sequon, demonstrating that DdPglB lacked the requirement for an acidic residue at the+2 position. Ielmini & Feldman (2011) also analysed the ability of DdPglB to transfer other glycans to AcrA and identified DATDH (2, 4-diacetamido-2,4,6-trideoxyhexose) as well as the E. coli O7 O-antigen polysaccharide, which contains an N-acetylglucosamine residue at the reducing end, as substrates for DdPglB. In addition to the CjPglB orthologues characterized to date, novel methods for high-throughput genome sequencing and an increased interest in micro-organisms from deepsea vent habitats have identified CjPglB orthologues in several novel species.…”
Section: Identification Of Novel Bacterial N-glycosylation Machineriementioning
confidence: 99%
See 1 more Smart Citation